Implementation of the Cooperative Creative Problem Solving (CPS) Model using Interactive LKPD to Improve Literacy Abilities and Learning Interest - Safitri, Violin Rahma; Hamidah, Hamidah; Nisa, Ratu Khoirotun; Kusuma, Jaka Wijaya (Tesseract: International Journal of Geometry and Applied Mathematics, 2025)
This study aims to analyze the effectiveness of the implementation of the Cooperative Creative Problem Solving (CPS) learning model assisted by interactive Student Worksheets (LKPD) in improving students' mathematical literacy skills and learning interest at SMP Negeri 16 Serang City. The study used a quasi-experimental design with a non-equivalent control group design. The sample consisted of two classes, namely the experimental class (n = 40) which was given CPS learning with interactive LKPD based on Live Worksheet, and the control class (n = 40) which used conventional learning. Data were collected through mathematical literacy tests and learning interest questionnaires given before and after the learning. The results of data analysis showed that the experimental class achieved a significant increase in mathematical literacy skills with an average N-gain of 0.7873 (high category), while the control class only achieved 0.4644 (medium category). Independent t-test analysis showed a significant difference between the two classes (p < 0.05). Furthermore, student learning interest in the experimental class also increased, with an average score of 86% (very strong category), higher than the control class's score of 70.75% (strong category). Thus, the CPS learning model assisted by interactive student worksheets (LKPD) has proven effective in improving students' mathematical literacy skills and learning interest. Educators are advised to widely implement this model, supported by digital media, to support active and meaningful learning.